A forebrain-hypothalamic ER stress driven circuit mediates hepatic steatosis during obesity - Katherine Blackmore; Claire J. Houchen; Hayk Simonyan; Hovhannes Arestakesyan; Alyssa K. Stark; Samantha A. Dow; Han Rae Kim; Jin Kwon Jeong; Anastas Popratiloff; Colin N. Young (Elsevier, 2024)
Objective: Non-alcoholic fatty liver disease (NAFLD) affects 1 in 3 adults and contributes to advanced liver injury and cardiometabolic disease. While recent evidence points to involvement of the brain in NAFLD, the downstream neural circuits and neuronal molecular mechanisms involved in this response, remain unclear. Here, we investigated the role of a unique forebrain-hypothalamic circuit in NAFLD. Methods: Chemogenetic activation and inhibition of circumventricular subfornical organ (SFO) neurons that project to the paraventricular nucleus of the hypothalamus (PVN; SFO→PVN) in mice were used to study the role of SFO→PVN signaling in NAFLD. Novel scanning electron microscopy techniques, histological approaches, molecular biology techniques, and viral methodologies were further used to delineate the role of endoplasmic reticulum (ER) stress within this circuit in driving NAFLD. Results: In lean animals, acute chemogenetic activation of SFO→PVN neurons was sufficient to cause hepatic steatosis in a liver sympathetic nerve dependent manner. Conversely, inhibition of this forebrain-hypothalamic circuit rescued obesity-associated NAFLD. Furthermore, dietary NAFLD is associated with marked ER ultrastructural alterations and ER stress in the PVN, which was blunted following reductions in excitatory signaling from the SFO. Finally, selective inhibition of PVN ER stress reduced hepatic steatosis during obesity. Conclusions: Collectively, these findings characterize a previously unrecognized forebrain-hypothalamic-ER stress circuit that is involved in hepatic steatosis, which may point to future therapeutic strategies for NAFLD.